Evolution, biogeography, and genetics of living tapirs - Pinho, Gabriela Medeiros; Lim, Qi Luan; Annavi, Geetha; da Silva, Anders Gonçalves; Saranholi, Bruno H. (Springer Nature, 2024)
Tapirs are among the oldest living large mammals, represented by only four widely recognized extant species: two in South America, one in Central America, and one in Southeast Asia. All species are in the genus Tapirus and are currently listed as vulnerable or endangered on the IUCN Red List of Threatened Species. This chapter builds on publications using genetic tools to reveal phylogenetic relationships among tapir species, intraspecific biogeography, and population patterns. We describe how genetic tools have been used by tapir researchers to date, discuss the limitations of published studies, and provide recommendations for future research.